Permian (Artinskian to Wuchapingian) conodont biostratigraphy in the Tieqiao section, Laibin area, South China - Sun, Yadong; Liu, X. T.; Yan, J. X.; Li, B.; Chen, B.; Bond, D. P G; Wignall, P. B.; Wang, X.; Lai, X. L.; Joachimski, Michael (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
Permian strata from the Tieqiao section (Jiangnan Basin, South China) contain several distinctive conodont assemblages. Early Permian (Cisuralian) assemblages are dominated by the genera Sweetognathus, Pseudosweetognathus and Hindeodus with rare Neostreptognathodus and Gullodus. Gondolellids are absent until the end of the Kungurian stage—in contrast to many parts of the world where gondolellids and Neostreptognathodus are the dominant Kungurian conodonts. A conodont changeover is seen at Tieqiao and coincided with a rise of sea level in the late Kungurian to the early Roadian: the previously dominant sweetognathids were replaced by mesogondolellids. The Middle and Late Permian (Guadalupian and Lopingian Series) witnessed dominance of gondolellids (Jinogondolella and Clarkina), the common presence of Hindeodus and decimation of Sweetognathus. Twenty main and seven subordinate conodont zones are recognised at Tieqiao, spanning the lower Artinskian to the middle Wuchiapingian Stage. The main (first appearance datum) zones are, in ascending order by stage: the Sweetognathus (Sw.) whitei, Sw. toriyamai, and Sw. asymmetrica n. sp. Zones for the Artinskian; the Neostreptognathodus prayi, Sw. guizhouensis, Sw. iranicus, Sw. adjunctus, Sw. subsymmeticus and Sw. hanzhongensis Zones for the Kungurian; the Jinogondolella (J.) nankingensis Zone for the Roadian; the J. aserrata Zone for the Wordian; the J. postserrata, J. shannoni, J. altudaensis, J. prexuanhanensis, J. xuanhanensis, J. granti and Clarkina (C.) hongshuiensis Zones for the Capitanian and the C. postbitteri Zone and C. transcaucasica Zone for the base and middle of the Wuchiapingian. The subordinate (interval) zones are the Pseudosweetognathus (Ps.) costatus, Ps. monocornus, Hindeodus (H.) gulloides, Pseudohindeodus ramovsi, Gullodus (G.) sicilianus, G. duani and H. excavates Zones. In addition, three new species, Gullodus tieqiaoensis n. sp., Pseudohindeodus elliptica n. sp. and Sweetognathus asymmetrica n. sp. are described. Age assignments for less common species (e.g., G. duani, H. catalanoi and Pseudosweetognathus monocornus etc.) are reassessed based on a rich conodont collection.
Keywords: Biostratigraphy; Cisuralian; Conodont; Guadalupian; Kungurian; South China